Research progress on the E protein of porcine reproductive and respiratory syndrome virus - Xiuqiao Chen; JingHua Pan; Liangzong Huang; Liangzong Huang; Mengmeng Zhao; Mengmeng Zhao (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is an economically important disease impacting the global pig industry, and it is characterized by reproductive disorder in sows and respiratory disorder in pigs of all ages. The PRRSV E protein is a nonglycosylated structural protein encoded by the ORF2b gene. The E protein is not necessary for the assembly of virus particles, but deletion of the E protein leads to transmissible virus particles not being produced. To better understand the structure and function of the E protein, we reviewed its genetic and evolutionary analysis, characteristics, subcellular localization and topology, ion channel activity, cellular immune response, additional biological functions, interactions with host proteins, interactions with PRRSV proteins, roles in infection, pathogenicity, and drugs. Therefore, this review can provide a theoretical basis for gaining an in-depth understanding of the E protein of PRRSV-2.